Администрирование и механизмы обеспечения безопасности SQL AZURE - Скляренко, С. Е.; Быков, П. И. (ХНУРЭ, 2011)
Every day we have to increasingly deal with concepts such as cloud technology, computing power, as well as data centers.SQL Azure is a powerful storage infrastructure, data management and analysis. The work is based on SQL Azure component Cloud Fabric, which in turn controls the database instance and ensures their deployment, administration, updating, monitoring and supporting the entire lifecycle of the data. Users are provided with only such tasks as creating a scheme and its maintenance, query optimization, and security management. Understanding of administration and security arrangements SQL Server, is one of the most important and pressing issues in information technology. In this regard, this report focuses on the study of these issues.
Keywords: облачные технологии; вычислительные мощности; центры хранения данных